SC6 Safer surgery through simulation. (November 2018) - Jaffry, Zahra; Jaye, Peter; Laws-Chapman, Colette; Zhao, Jade; Pontin, Linnie
Abstract : Background: A significant morbidity and mortality rate is attributable to surgical errors. The extension of the World Health Organisation Surgical Safety Checklist, known as the 5 Steps to Safer Surgery (5SSS), ¹ is designed to minimise this but a lack of compliance with these steps has been demonstrated in local audits and reports by the Care Quality Commission, particularly in para-surgical specialities, such as Interventional Radiology (IR). Therefore, we created a training programme to address this. Summary of education programme: A half day programme was run for doctors, nurses and radiologists in the IR department. It started with an introduction to the 5SSS, Human Factors (HF) and their contribution to preventing errors and enhancing safety. A simulation-based scenario then ran in the IR lab to allow repeat cycle deliberate practice of the 5SSS with the opportunity to interrupt and suggest changes to the checklist that could localise it and improve implementation. These were then shared with departmental leads. Summary of results: 31% of doctors, 36% of nurses and 20% of radiographers attended. The effect was measured though pre and post participant questionnaires and audits on compliance with the 5SSS. The questions looked at development in two categories: attitude towards the 5SSS, including confidence in using it and opinions on its value; self–efficacy in HF skills, measured by the validated Human Factors in Healthcare Instrument. ² There was a significant improvement in the former (p<0.00001) and in being able to 'constructively manage others' negative emotions at work', 'communicate effectively with a colleague with whom you disagree' and 'deal with uncertainty in the decision-making process' (p<0.05). Results from the audit showed an improvement in compliance in all areas of the 5SSS, most significantly in 'all three stages of the checklist being done at the correct time', which increased by 23%. Trust-wide this figure was only 10%. Discussion, conclusion and recommendations: The driving force towards compliance with the 5SSS and an enhanced safety culture is the attitude and skills of the staff that work within the organisation. This can be influenced by in-situ simulation based training programmes, such as this one, that emphasise the importance of safety measures and empower staff to make changes to implement them effectively. References: National Patient Safety Agency. 'How to guide' five steps to safer surgery 2010. London: NPSA. Available at: http://www.nrls.npsa.nhs.uk/resources/?EntryId45=92901 Reedy GB, Lavelle M, Simpson T, Anderson JE. Development of the human factors skills for healthcare instrument: A valid and reliable tool for assessing interprofessional learning across healthcare practice settings. BMJ Simulation and Technology Enhanced Learning 2017;3(4):135–141.